Morning of the Actresses. Anca Hațiegan, “Dimineața Actrițelor [Morning of the Actresses]” (Iași: Polirom, 2019) - SAS-MARINESCU, Raluca (Studia Universitatis Babeș-Bolyai Dramatica, 2019)
Romanian theatre history is short however the studies, books and research - we mean those worthy to consider - are rare. This is why a book like Anca Hațiegan's Morning of the actresses is more than welcome among theatre specialists. But the great contribution comes only now: it is a book about the very beginning of female acting in Romania written in a style full of warm and humor, so that it can be read by anyone, using a language adapted to the story extraction era to facilitate reading. What the book does is to return the respect for the women at the beginning of the century, that fought to have the recognition of their presence on stage and to give them the recognition that they deserve. Divided into seven chapters the book is trying - successfully I may add - to recompose an era when the calling of being an actress is an obloquy. The picture is a complex one because we have a chapter about the first female critic or a chapter about the female students of the first drama schools from Romania. The big plus of the research is that it's not only a series of portraits, as expected, but it creates and anecdotal atmosphere, full of conspiracy and obstacles put in the way of these women. It follows the destinies of the first females who risked their reputations to play on stage, from time to time in intimate details, that are selected by the author with the purpose of explaining the circumstances - sociological, political, family, perceptions - in which the professional actress appears in Romania and the circumstances that lead to the disappearance of some of them: Romanian women agreed with this hypostasis of "mothers of the nation and family" because it facilitated their penetration into the public sphere.[1] [1] Anca Hațiegan, Dimineața Actrițelor [Morning of the Actresses] (Iași: Polirom, 2019), 53.